2022
DOI: 10.1177/10776990221084606
|View full text |Cite
|
Sign up to set email alerts
|

How Misinformation and Rebuttals in Online Comments Affect People’s Intention to Receive COVID-19 Vaccines: The Roles of Psychological Reactance and Misperceptions

Abstract: This study investigated how exposure to negative and misleading online comments about the COVID-19 vaccination persuasive messages and the ensuing corrective rebuttals of these comments affected people’s attitudes and intentions regarding vaccination. An online experiment was performed with 344 adults in the United States. The results showed that rebuttals by the Centers for Disease Control and Prevention, rather than those by social media users, indirectly increased people’s willingness to receive the vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…This is based on prior (Hwang & Jeong, 2023). This is in addition to the findings showing that rebuttals by the specialized official sources, rather than those by social media users, indirectly increased people's willingness to receive the vaccine by reducing their psychological reaction to persuasive messages and their belief in the misinformation contained in the comments (Sun & Lu, 2023).…”
Section: ‫لبحوث‬ ‫العلمية‬ ‫المجلة‬ ‫والتليفزيون‬ ‫اإلذاعة‬mentioning
confidence: 62%
“…This is based on prior (Hwang & Jeong, 2023). This is in addition to the findings showing that rebuttals by the specialized official sources, rather than those by social media users, indirectly increased people's willingness to receive the vaccine by reducing their psychological reaction to persuasive messages and their belief in the misinformation contained in the comments (Sun & Lu, 2023).…”
Section: ‫لبحوث‬ ‫العلمية‬ ‫المجلة‬ ‫والتليفزيون‬ ‫اإلذاعة‬mentioning
confidence: 62%
“…This was another optimistic finding as it suggests the possibility that fact-checks could be effective even for misleading content that is congruent with one's political worldview. In contrast to the previous studies that focused on political issues and topics, Sun and Lu (2023) focused on a health context (i.e., COVID-19) and examined the efficacy of direct rebuttals of misinformation by different sources rather than fact-check labels. The results found that such rebuttals from credible sources (i.e., Centers for Disease Control and Prevention) can work indirectly by reducing beliefs in misinformation, which lead to greater vaccination intention.…”
Section: Effectiveness Of Countermeasures Against Misinformationmentioning
confidence: 99%
“…Reactance involves both cognitive and emotional responses, prompting behaviors aimed at regaining one's sense of autonomy [19]. Previous studies have found that psychological reactance plays a significant role in how people cope with attempts to correct health misinformation on social media [74,87,115]. Specifically, it affects the effectiveness of fact-checking corrections and misinformation warning labels [99,109,140].…”
Section: Efficiency Of the Correction Measures And Reactance Theorymentioning
confidence: 99%